Effect of repeated active recovery during a high-intensity interval-training shock microcycle on markers of fatigue - Wiewelhove, T.; Raeder, C.; Meyer,T.; Kellmann, M.; Pfeiffer, M.; Ferrauti, A. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To investigate the effect of repeated use of active recovery during a 4-d shock microcycle with 7 high-intensity interval-training (HIT) sessions on markers of fatigue.